Upaya Mengembangkan Kemampuan Motorik Halus Anak melalui Pemanfaatan Bahan Bekas dalam Pembelajaran di Kelompok B RA Ar-Rafif Kalasan, Sleman, Yogyakarta. - Afifah Fatihakun Ni'mah; Erni Munastiwi (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2019)
The purpose of this research to find the efforts of development children’s motor fine skills in group B RA Ar-Rafif, Kalasan, Sleman, Yogyakarta through utilization of used materials. The type of this research is collaborative classroom action research which is uses research model by Kurt Levin. The Method of collect data are observation, interviews, and documentation. The current data analysis are descriptive, qualitative, and quantitative. The Indicator of success minimum is very high category and children’s motor fine skills minimum 85% which develop as expected category (develop as expected and develop very well) from 12 children. This research was conducted in two cycles, each cycle consist of three meetings. The Research process are planning, implementation, observation, and reflection. The results showed that: First, development children’s motor fine skills before given action 16,67% which develop as expected category (develop as expected and develop very well), the ability motor fine skills of childhood less optimal. Second, implementation utilization of used materials in learning in group B RA Ar-Rafif Kalasan can increase children’s motor fine skills. Third, development children motor fine skills after given action an increase cycle 1 of 50% (develop as expected and develop very well) and increase cycle 2 of 91,66% (develop as expected and develop very well).